2016
DOI: 10.4993/acrt.24.1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in targeted therapy and immunotherapy for treatment of lung cancer

Abstract: Personalized therapy based on targetable genetic aberrations has become a standard therapy for cases of lung adenocarcinoma (LADC) harboring EGFR mutations and ALK fusions. The effects of such personalized therapy are significantly positive with a higher response rate and longer survival compared to conventional chemotherapy. Therefore, further identification of druggable genetic aberrations and the development of molecular targeting drugs for them are required. For LADC, several new targeted drugs against dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Targeted therapy according to next generation sequencingbased panel sequencing tations and ALK, RET, and ROS1 fusions is necessary. We and others have reported that gene mutation profiles differ even in different histological cancer subtypes 17,18) . Therefore, it is necessary to select the appropriate sequencing panel for each patient, in order to determine actionable gene mutations to perform personalized targeted therapy.…”
Section: Clinical Sequencing Panelmentioning
confidence: 85%
“…Targeted therapy according to next generation sequencingbased panel sequencing tations and ALK, RET, and ROS1 fusions is necessary. We and others have reported that gene mutation profiles differ even in different histological cancer subtypes 17,18) . Therefore, it is necessary to select the appropriate sequencing panel for each patient, in order to determine actionable gene mutations to perform personalized targeted therapy.…”
Section: Clinical Sequencing Panelmentioning
confidence: 85%